Expression of β2 adrenoreceptors on peripheral blood mononuclear cells in patients with primary and secondary progressive multiple sclerosis: a longitudinal six month study. Issue 2 (1st February 2003) - Zoukos, Y; Thomaides, T N; Kidd, D; Cuzner, M L; Thompson, A
Abstract : Background: β2 Adrenoreceptor expression on peripheral blood mononuclear cells is increased in progressive multiple sclerosis. This increase has been correlated with disease activity in relapsing-remitting multiple sclerosis. Objective: To determine the β2 adrenoreceptor expression in primary and secondary progressive multiple sclerosis in relation to findings on magnetic resonance imaging (MRI) and clinical disease activity. Methods: 10 patients with multiple sclerosis were studied (five with primary progressive and five with secondary progressive forms of the disease) over a period of six months. Monthly clinical and MRI assessments of the brain and spinal cord were carried out. β2 Adrenoreceptor expression was assessed monthly using a ligand binding assay with [ 125 I]iodocyanopindolol. Expression of β2 adrenoceptors on peripheral blood mononuclear cells was also assessed in five normal controls over a similar period. Results: The mean (SEM) value of β2 adrenoreceptor density for the five normal controls was 1346 (183) sites/cell, with affinity Kd of 120 (40) pM. MRI disease activity in primary progressive multiple sclerosis was reported on two occasions and on those occasions the expression of β2 adrenoreceptors was increased in excess of 1900 sites/cell; in the remaining 28 observations β2 adrenoreceptor expression was within the normal range (800 to 1900 sites/cell). In patients with secondary progressive disease, MRI disease activity was observed on 16 occasions. In these patients expression of β2 adrenoreceptors was increased in excess of 2000 sites/cell in all measurements except in one subject who did not show MRI activity throughout the six months period of study. The affinity of the receptors was within the normal range in all cases. Conclusions: Increased expression of β2 adrenoreceptors was correlated with MRI disease activity in two patients with primary progressive multiple sclerosis. In secondary progressive multiple sclerosis, increased expression of β2 adrenoreceptors tended not to correlate with MRI disease activity. This may reflect a persistent Th1 immune reaction in the secondary progressive form of the disease.